(untitled) (Challenges of the Future, 2024)
Research Question (RQ): This paper focuses on: a) What are the main challenges and barriers universities face when attempting to fulfil their social responsibility, and b) What innovative approaches or best practices can be identified to overcome these obstacles and enhance their social impact? b) How do universities measure and report on their social responsibility initiatives, and what are the key indicators and metrics used to assess the effectiveness and impact of these programs? c) What are the key dimensions and components of social responsibility for universities, and how do they vary across different cultural and institutional contexts? Purpose: The research purpose and goal of studying the social responsibility of universities is to better understand, assess, and improve the impact of these institutions on society, the environment, and their local communities. This study also aims to inspire positive change, promote accountability, and contribute to the broader goals of sustainability and ethical leadership in education. Method: The method used is mainly the analytical approach, with conceptual analysis and examination of arguments. The research material focuses on various articles, reports, and relevant literature on the issue under consideration. The research material also includes the administration of 30 semi-structured interviews with lecturers who agreed to share their attitudes and perceptions on the issues. Results: The findings indicate that institutions, on their part, must change their approach towards society, the philosophy of being only in the function of student preparation and scientific research, but take responsibility towards society. Organisation: To maximise the impact of university research on managers, organisations, and practices, there is often a need for effective knowledge transfer mechanisms, such as research dissemination, industry-academia partnerships, and knowledge exchange programs. Universities, businesses, and policymakers often collaborate to facilitate the practical application of research findings and ensure that research is accessible and relevant to those who can benefit from it. Society: The concept of social responsibility at universities, often referred to as the civic or public mission of universities, can have a significant research impact on society, social responsibility, and the environment. This concept emphasises that universities should actively engage with and contribute to their communities and the wider world. Originality: The social responsibility of universities extends beyond education and research. It encompasses a commitment to contribute to the well-being of society and the environment. By embracing this concept, universities can enhance the impact of their research on these critical areas, fostering positive change and sustainability. For Albanian higher education, it is a challenge because it is necessary to intervene in the legal framework in force by drafting acts of criteria for their identification and measurable indicators. Limitations and further research: It is necessary to undertake a more in-depth study with a more comprehensive approach, where data, considerations, and different actors involved in the role of universities in facing the challenges stemming from social problems and sustainability are highlighted.